A composite water vapor barrier membrane
By designing a three-dimensional interlocking structure between the inorganic barrier layer and the organic polymer layer, the problem of easy cracking of the water vapor barrier film during bending is solved, achieving more durable water vapor barrier performance and transparency, which is suitable for the encapsulation of flexible perovskite solar cells and other high humidity sensitive electronic devices.
Patent Information
- Application Number
- CN202522273289.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2035-10-28
AI Technical Summary
Existing water vapor barrier films are prone to cracking during bending, leading to degradation of barrier performance and affecting the lifespan and stability of flexible thin-film solar cells.
The composite water vapor barrier membrane with a three-dimensional interlocking structure achieves the interlocking of the inorganic and organic layers by forming protrusions on the surface of the inorganic barrier layer and grooves on the surface of the organic polymer layer. This enhances the interfacial bonding force and relieves stress, forming a honeycomb or mortise and tenon structure to increase the length of the gas diffusion path.
It effectively extends the durability of the moisture barrier film, maintains excellent moisture barrier properties and optical transmittance, and is suitable for encapsulation protection of flexible perovskite solar cells and other high humidity-sensitive electronic devices.
Smart Images

Figure CN224942549U_ABST
Abstract
Description
Technical Field
[0001] This application relates to the fields of water vapor barrier film materials and optoelectronic packaging technology, and in particular to a composite water vapor barrier film suitable for the packaging and protection of flexible perovskite solar cells and other highly humidity-sensitive electronic devices. Background Technology
[0002] Flexible thin-film solar cells possess excellent flexibility and thinness, making them widely used in solar backpacks, solar tents, solar flashlights, solar cars, and building-integrated photovoltaics (BIPV). Existing flexible thin-film solar cells typically use organic polymer substrate films (such as high-transmittance PET or PC substrate films). However, existing organic polymer substrate films have relatively poor moisture permeability, allowing water vapor and oxygen to more easily penetrate into the flexible thin-film solar cell, easily causing water and oxygen aging and failure of the internal structure. In summary, the water vapor barrier performance of the organic polymer substrate film determines the lifespan and stability of flexible thin-film solar cells.
[0003] To improve the water vapor barrier performance of organic polymer substrate films, existing technologies involve depositing an inorganic barrier layer on the organic polymer substrate film. Known inorganic barrier layers include SiN... x While substances such as Al2O3, ZnO, and MgO can improve the barrier properties of organic polymer base films, the water vapor barrier film formed by the organic polymer base film / inorganic barrier layer is prone to cracking during bending.
[0004] To address the issue of water vapor barrier films being prone to cracking due to bending caused by the deposition of inorganic barrier layers, existing improvements involve using PET as a substrate and depositing SiN on its surface. x SiO x Alternatively, an inorganic barrier layer, such as Al2O3, may be formed before an organic polymer layer is created. However, in the traditional planar structure of organic polymer substrate film / inorganic barrier layer / organic polymer layer, the interfacial bonding between the organic and inorganic layers is weak, making it prone to microcracks during bending or thermal cycling, leading to degradation of the water vapor barrier membrane's barrier performance. Furthermore, a purely planar interface cannot effectively alleviate interfacial stress, especially in flexible applications where delamination is more likely to occur, further degrading the water vapor barrier membrane's barrier performance. In summary, existing water vapor barrier membranes suffer from a problem of inconsistent water vapor barrier durability. Utility Model Content
[0005] To address the persistent deviation in water vapor barrier properties of existing water vapor barrier membranes, this application provides a composite water vapor barrier membrane.
[0006] The composite water vapor barrier membrane provided in this application is achieved through the following method:
[0007] A composite water vapor barrier membrane has a layer structure comprising an organic polymer base membrane, an inorganic barrier layer, and an organic polymer layer. The inorganic barrier layer has a plurality of protrusions on its surface. The organic polymer base membrane has a plurality of first grooves on its surface facing the inorganic barrier layer. The organic polymer layer has a plurality of second grooves on its surface facing the inorganic barrier layer. The protrusions on one surface of the inorganic barrier layer are fitted into the first grooves, and the protrusions on the other surface of the inorganic barrier layer are fitted into the second grooves.
[0008] This application utilizes a three-dimensional interlocking composite interface to enhance interlayer bonding, effectively alleviate interfacial stress, effectively curb the degradation of the water vapor barrier film's barrier performance, extend the water vapor barrier film's water vapor barrier durability, and maintain excellent water vapor barrier properties and optical transmittance. It is suitable for the encapsulation and protection of flexible perovskite solar cells and other high humidity-sensitive electronic devices.
[0009] Preferably, the protrusions are distributed in a dot matrix pattern on the surface of the inorganic barrier layer.
[0010] Preferably, the protrusion is a tenon structure; the first groove is a mortise groove; and the second groove is a mortise groove.
[0011] Preferably, the protrusion is a honeycomb protrusion; the first groove structure is a honeycomb groove; and the second groove is a honeycomb groove.
[0012] Preferably, the height of the protrusion toward the inorganic barrier layer is equal to 0.05-0.25 times the thickness of the inorganic barrier layer; the height of the protrusion toward the organic polymer layer is equal to 0.05-0.25 times the thickness of the organic polymer layer.
[0013] By adopting the above technical solutions, the water vapor barrier durability of the water vapor barrier membrane can be better extended.
[0014] Preferably, the inorganic barrier layer is SiN. x Barrier layer, SiN x The thickness of the barrier layer is 40-80nm.
[0015] Preferably, the inorganic barrier layer comprises SiN x Barrier layer and ZnO barrier layer, the ZnO barrier layer is located adjacent to SiN x Between the barrier layers, monolayer SiN x The thickness of the barrier layer is 5-20 nm; the thickness of the single-layer ZnO barrier layer is 5-20 nm.
[0016] By adopting the above technical solution, the composite water vapor barrier membrane is given a better water vapor barrier effect.
[0017] Preferably, the organic polymer layer has a contact angle ≥150°, a roll-off angle ≤10°, and a refractive index of 1.35-1.45.
[0018] Preferably, the organic polymer layer is a dodecafluoroheptyl methacrylate polymer coating; the thickness of the dodecafluoroheptyl methacrylate polymer coating is 0.5-2 μm.
[0019] Preferably, the organic polymer base film is selected from any one of PET film, polyimide PI film, polypropylene PP film, polyethylene PE film, polycarbonate PC film, polyethylene naphthalate PEN film, polymethyl methacrylate PMMA film, and polystyrene PS film.
[0020] In summary, this application has the following advantages:
[0021] 1. This application uses a three-dimensional interlocking composite interface to enhance interlayer bonding, effectively alleviate interfacial stress, effectively curb the degradation of the water vapor barrier membrane's barrier performance, extend the water vapor barrier membrane's water vapor barrier durability, and maintain excellent water vapor barrier properties and optical transmittance.
[0022] 2. The water vapor barrier membrane of the present invention has high barrier properties: the honeycomb micropores and tenon-and-mortise morphology increase the gas diffusion path length and improve the barrier performance.
[0023] 3. The water vapor barrier membrane of the present invention has excellent flexibility: the staggered interlocking periodic structure can effectively disperse the stress concentration area and improve the overall flexibility and crack resistance.
[0024] 4. The water vapor barrier membrane of the present invention has staggered stress dispersion: both the inorganic layer and the polymer layer are optically transparent materials, which do not affect the light absorption performance of optoelectronic devices.
[0025] 5. The water vapor transmission rate (WVTR) of the composite water vapor barrier membrane in this application is ≤1×10⁻ 5 g·m⁻²·day⁻¹; performance retention rate ≥90% after 500 cycles under a bending radius of 5 mm. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the layer structure of the composite water vapor barrier membrane in Example 1.
[0027] Figure 2 This is a schematic diagram of the layer structure of the composite water vapor barrier membrane in Example 3.
[0028] Figure 3 This is a schematic diagram of the layer structure of the composite water vapor barrier membrane in Comparative Example 1.
[0029] In the figure, 1 is the organic polymer substrate film; 11 is the first groove; 2 is the inorganic barrier layer; 21 is the protrusion; and 201 is SiN. xBarrier layer; 202, ZnO barrier layer; 3, organic polymer layer; 31, second groove. Detailed Implementation
[0030] The technical solution of this application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Example 1: Refer to Figure 1 A composite water vapor barrier membrane structure consists of an organic polymer base membrane 1, an inorganic barrier layer 2, and an organic polymer layer 3.
[0032] The organic polymer base film 1 is selected from any one of PET film, polyimide (PI) film, polypropylene (PP) film, polyethylene (PE) film, polycarbonate (PC) film, polyethylene naphthalate (PEN) film, polymethyl methacrylate (PMMA) film, and polystyrene (PS) film. In this embodiment, the organic polymer base film 1 is selected from optical PET film.
[0033] The inorganic barrier layer 2 can be a single-layer inorganic barrier layer or a multi-layer composite inorganic barrier layer, wherein the inorganic material is selected from at least one of silicon oxide, aluminum oxide, silicon nitride, zinc oxide, zirconium oxide, magnesium oxide, titanium oxide, montmorillonite, hafnium oxide, and indium tin oxide. In this embodiment, the inorganic barrier layer 2 is SiN. x The barrier layer is prepared using existing hot-wire CVD deposition technology.
[0034] Organic polymer layer 3, also known as the organic polymer barrier layer, is used to improve overall flexibility and stress matching between multiple layers. The organic polymer barrier layer is at least one of parylene, polytetrafluoroethylene, polyethylene glycol aluminum, polyglycidyl methacrylate, epoxy resin, polyimide, polysiloxane, and dodecyl fluoroheptyl methacrylate. In this embodiment, organic polymer layer 3 is a dodecyl fluoroheptyl methacrylate barrier layer formed by UV curing of dodecyl fluoroheptyl methacrylate, with a thickness of 2 μm, prepared using the existing spin-coating method.
[0035] The specific layer structure of the composite water vapor barrier film is an optical PET film (organic polymer substrate film 1) and a 50nm thick SiN film deposited by ALD process. x Barrier layer (inorganic barrier layer 2), and organic polymer layer 3 with a thickness of 2 μm formed by spin coating of dodecafluoroheptyl methacrylate followed by UV curing.
[0036] Reference Figure 1The surface of the barrier layer 2 is formed with a plurality of protrusions 21 distributed in a dot matrix by nanoimprinting. The surface of the organic polymer base film 1 facing the inorganic barrier layer 2 is formed with a plurality of first grooves 11 distributed in a dot matrix by nanoimprinting. The surface of the organic polymer layer 3 facing the inorganic barrier layer 2 is formed with a plurality of second grooves 31 distributed in a dot matrix by nanoimprinting. The protrusions 21 on one surface of the inorganic barrier layer 2 are fitted into the first grooves 11, and the protrusions 21 on the other surface of the inorganic barrier layer 2 are fitted into the second grooves 31.
[0037] Reference Figure 1 The protrusion 21 is a tenon structure with a diameter of 5 nm and a height of 10 nm. The spacing between adjacent tenons is 50 nm. The first groove 11 is a mortise groove with a diameter of 5 nm and a groove depth of 10 nm. The second groove 31 is a mortise groove with a diameter of 5 nm and a groove depth of 10 nm.
[0038] The difference between Example 2 and Example 1 is that: the protrusion 21 is a honeycomb protrusion with a side length of 4nm and a height of 10nm. The spacing between adjacent honeycomb protrusions is 50nm. The first groove 11 is a honeycomb groove with a side length of 4nm and a groove depth of 10nm in its vertical projection. The second groove 31 is a honeycomb groove with a side length of 4nm and a groove depth of 10nm in its vertical projection.
[0039] The difference between Example 3 and Example 1 is that: (Refer to...) Figure 2 The inorganic barrier layer 2 comprises two SiN layers. x Barrier layer 201 and a ZnO barrier layer 202, wherein the ZnO barrier layer 202 is located adjacent to SiN x Between the barrier layer 201, a single layer of SiN x The barrier layer 201 has a thickness of 20 nm; the single-layer ZnO barrier layer 202 has a thickness of 20 nm. The protrusion 21 is a tenon structure with a diameter of 2.5 nm and a height of 5 nm. The spacing between adjacent tenons is 25 nm. The first groove 11 is a mortise groove with a diameter of 2.5 nm and a depth of 5 nm. The second groove 31 is a mortise groove with a diameter of 2.5 nm and a depth of 5 nm.
[0040] The difference between Example 4 and Example 1 is that the inorganic barrier layer 2 includes two layers of SiN. x Barrier layer 201 and a ZnO barrier layer 202, wherein the ZnO barrier layer 202 is located adjacent to SiN x Between the barrier layer 201, a single layer of SiN xThe thickness of the barrier layer 201 is 20 nm; the thickness of the single-layer ZnO barrier layer 202 is 20 nm. The protrusions 21 are honeycomb protrusions, with a side length of 2 nm and a height of 5 nm. The spacing between adjacent honeycomb protrusions is 25 nm. The first groove 11 is a honeycomb groove, with a side length of 2 nm and a groove depth of 5 nm in its vertical projection. The second groove 31 is a honeycomb groove, with a side length of 2 nm and a groove depth of 5 nm in its vertical projection.
[0041] Comparative Example 1: See Figure 3 The specific layer structure of the composite water vapor barrier film is an optical PET film (organic polymer substrate film 1), and a 50nm thick SiN film deposited by hot-wire CVD deposition process. x Barrier layer (inorganic barrier layer 2), and organic polymer layer 3 with a thickness of 2 μm formed by spin coating of dodecafluoroheptyl methacrylate followed by UV curing.
[0042] Table 1: Performance parameters of the composite water vapor barrier membranes in Examples 1-4 and Comparative Example 1
[0043] Total thickness Water vapor barrier ratio (WVTR) g·m⁻²·day⁻¹ Transmittance % (400-800 nm) Change in water vapor barrier efficiency after 500 bends (g·m⁻²·day⁻¹) Example 1 380 nm <![CDATA[6.54×10 ⁻5 ]]> 92 <![CDATA[9.26×10 ⁻5 ]]> Example 2 380 nm <![CDATA[7.52×10 ⁻5 ]]> 90 <![CDATA[8.86×10 ⁻5 ]]> Example 3 380 nm <![CDATA[6.27×10 ⁻5 ]]> 94 <![CDATA[7.33×10 ⁻5 ]]> Example 4 380 nm <![CDATA[5.12×10 ⁻5 ]]> 92 <![CDATA[5.58×10 ⁻5 ]]> Comparative Example 1 380 nm <![CDATA[8.53×10 ⁻4 ]]> 91 <![CDATA[5.32×10 ⁻3 ]]>
[0044] Note: The water vapor transmission rate of the composite water vapor barrier membrane was determined according to GB / T 30412-2013 "Determination of water vapor transmission rate of plastic films and sheets - Humidity sensor method".
[0045] As can be seen from Examples 1-3 and the comparative examples and Table 1, the mortise and tenon / honeycomb composite water vapor barrier structure of this utility model significantly improves the interfacial bonding force while maintaining flexibility and light transmittance, effectively alleviates interfacial stress, effectively curbs the degradation of the barrier performance of the water vapor barrier film, and prolongs the water vapor barrier durability of the water vapor barrier film. It is suitable for the encapsulation and protection of flexible perovskite solar cells and other high humidity sensitive electronic devices.
[0046] The embodiments described in this specific implementation are preferred embodiments of this application and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A composite water vapor barrier membrane, characterized in that: The composite water vapor barrier membrane has a layer structure of an organic polymer base membrane (1), an inorganic barrier layer (2), and an organic polymer layer (3). The surface of the inorganic barrier layer (2) has a plurality of protrusions (21). The surface of the organic polymer base membrane (1) facing the inorganic barrier layer (2) has a plurality of first grooves (11). The surface of the organic polymer layer (3) facing the inorganic barrier layer (2) has a plurality of second grooves (31). The protrusions (21) on one surface of the inorganic barrier layer (2) are fitted into the first grooves (11), and the protrusions (21) on the other surface of the inorganic barrier layer (2) are fitted into the second grooves (31).
2. The composite water vapor barrier membrane according to claim 1, characterized in that: The protrusions (21) are distributed in a dot matrix pattern on the surface of the inorganic barrier layer (2).
3. The composite water vapor barrier membrane according to claim 1, characterized in that: The protrusion (21) is a tenon structure; the first groove (11) is a mortise groove; the second groove (31) is a mortise groove.
4. The composite water vapor barrier membrane according to claim 1, characterized in that: The protrusion (21) is a honeycomb protrusion; the first groove (11) has a honeycomb groove structure; the second groove (31) is a honeycomb groove.
5. The composite water vapor barrier membrane according to claim 1, characterized in that: The height of the protrusion (21) facing the inorganic barrier layer (2) is equal to 0.05-0.25 times the thickness of the inorganic barrier layer (2); the height of the protrusion (21) facing the organic polymer layer (3) is equal to 0.05-0.25 times the thickness of the organic polymer layer (3).
6. The composite water vapor barrier membrane according to claim 1, characterized in that: The inorganic barrier layer (2) is SiN x Barrier layer, SiN x The thickness of the barrier layer is 40-80nm.
7. The composite water vapor barrier membrane according to claim 1, characterized in that: The inorganic barrier layer (2) includes SiN x Barrier layer (201) and ZnO barrier layer (202), the ZnO barrier layer (202) being located adjacent to SiN x Between the barrier layers (201), a single layer of SiN x The thickness of the barrier layer (201) is 5-20 nm; the thickness of the single-layer ZnO barrier layer (202) is 5-20 nm.
8. The composite water vapor barrier membrane according to claim 1, characterized in that: The organic polymer layer (3) has a contact angle ≥150°, a roll-off angle ≦10°, and a refractive index of 1.35–1.
45.
9. A composite water vapor barrier membrane according to claim 8, characterized in that: The organic polymer layer (3) is a dodecafluoroheptyl methacrylate polymer coating; the thickness of the dodecafluoroheptyl methacrylate polymer coating is 0.5-2 μm.
10. A composite water vapor barrier membrane according to claim 8, characterized in that: The organic polymer base film (1) is selected from any one of PET film, polyimide PI film, polypropylene PP film, polyethylene PE film, polycarbonate PC film, polyethylene naphthalate PEN film, polymethyl methacrylate PMMA film, and polystyrene PS film.
